Effect of Crystallinity of Apatite in Cremated bone on Carbon exchanges during burial and reliability of Radiocarbon Dating. Issue 6 (19th August 2019) - Minami, M; Mukumoto, H; Wakaki, S; Nakamura, T
ABSTRACT: This study characterized cremated bone to better understand isotope exchanges during burial, using archeological samples. The cremated bones of Jokei, a Buddhist monk (AD 1155–1213), found in an urn from the Jisho-in Temple, Nara Prefecture, Japan, were used for the analysis. 14 C dates were determined for eight of Jokei bone fragments of different colors (black, gray, and white). The white fragments had the highest x-ray diffractometry (XRD) crystallinity index (CI) values (0.89–1.05), Fourier-transform infrared spectroscopy (FTIR) splitting factor values (IRSF) of 5.3–7.1, and the lowest Ba concentrations. The calibrated date of the white bone fragments is 1152–1216 cal AD, consistent with Jokei's lifespan, showing these fragments yield reliable 14 C ages. Meanwhile, the black and gray fragments, which probably experienced lower temperatures during cremation, had lower CI and IRSF values of 0.25–0.46 and 4.2–4.9, respectively, and higher Ba concentrations. The black and gray fragments tended to show unreliable younger 14 C dates and higher 87 Sr/ 86 Sr values close to the soil value due to soil contamination. The results in this study indicate that it is important to check crystallinity of apatite and soil contamination using chemical indexing methods such as Ba capture, to clarify the reliability of 14 C dates for cremated bone samples.